Dark Matter; Modification of f (R) or Wimps Miracle - Övgün, Ali (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: The identity of dark matter is one of the key outstanding problems in both particle and astrophysics. In this thesis, I review some candidates of dark matter, especially WIMPs (weakly interacting massive particles) which is one of the best candidate so it is called that WIMPs miracle. In addition of this, there are also some theories of modification of gravity, by changing the law of gravity, it could be possible that the dark matter observations are explained. Until the dark matter particle is detected, there is some room for uncertainty. So we should consider every part of the problem and solve it. Dark matter problem is covering a large area so every possibility is important. So f (R) gravity is also reviewed in this thesis and some theories are considered as a possible solution of dark matter problem. Finally we highlight that, even in the case of WIMPs or another particles solution, f (R) gravity is also can be used for this problem. However, last words will be said by experiments. Keywords: Dark Matter, Weakly Interacting Particles(WIMPs), f (R) Gravity, Cosmology. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Karanlık Maddenin gizemi hem astrofizik hem de parc¸acık fiziği açısından çok önemli bir problemdir. Bu tezde, karanlık madde adaylarını, özellikle WIMPs mucizesi olarak bilinen ve en güçlü aday olan WIMPs (zayıf etkiles¸en kütleli parçacık)i inceledim. Karanlık Maddenin gizemini cözmeye çalışan bundan başka teoriler de vardır, örneğin gravitasyonun modifiye edilmesi gibi. Karanlık madde parçacıkları deneylerde bulunana kadar, bu gizem sürecektir. Biz bu gizemi her açıdan inceleyip çözüm üretmemiz gerekir çünkü çok geniş bir alanı kapsayan bu alan için her bir ihtimal bile çok önemlidir. Karanlık maddeyi açıklamaya aday olan f (R) gravitasyon teorisini de bu tezde inceledik ve çözüm üretmeye çalıştık. Sonuç olarak, gerek WIMPs olsun gerekse bas¸ka parçacıklar olsun, f (R) gravistasyon teorisi de güzel bir alternatiftir ve kullanılabilir. Tabii hangisinin doğru olduğunu deneyler onaylaycak. Anahtar Kelimeler: Karanlık Madde, Zayıf Etkileşen Kütleli Parçacıklar (WIMPs), f (R) Gravistasyon Teorisi, Kozmoloji.
Master of Science in Physics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2012. Supervisor: Prof. Dr. Mustafa Halilsoy.
Keywords: Physics; Dark Matter (Astronomy); Cosmology - Physics; Dark Matter - Weakly Interacting Particles (WIMPs) - f (R) Gravity - Cosmology